New Library Buildings and Library Reconstructions - Larsen, Steen Bille; Niederer, Ulrich (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Visits to libraries have always been an important part of the LIBER Architecture Group Seminars, as they add practice, concrete examples of success and mistakes to the theory of the seminar presentations. The programme of the Leipzig seminar thus offered quite a few library visits: Universitätsbibliothek Leipzig, Thüringer Universitäts- und Landesbibliothek, Jena, Universitäts- und Forschungsbibliothek Erfurt, Herzogin-Anna-Amalia-Bibliothek, Weimar, Universitätsbibliothek der Bauhaus-Universität Weimar, Deutsche Bücherei, Leipzig and Sächsische Landesbibliothek – Staatsund Universitätsbibliothek, Dresden. The following is a short report about the libraries visited during the week. The reports are combined with quotations from the libraries’ presentation of their building projects and in some cases also with facts and figures.